2020
DOI: 10.4049/jimmunol.1901100
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4s in Teleosts: Two Paralogous Chemokine Receptors and Their Roles in Hematopoietic Stem/Progenitor Cell Homeostasis

Abstract: Hematopoietic stem/progenitor cells (HSPCs) generate the entire repertoire of immune cells in vertebrates and play a crucial role during infection. Although two copies of CXC motif chemokine receptor 4 (CXCR4) genes are generally identified in teleosts, the function of teleost CXCR4 genes in HSPCs is less known. In this study, we identified two CXCR4 genes from a teleost, ayu (Plecoglossus altivelis), named PaCXCR4a and PaCXCR4b. PaCXCR4b was constitutively expressed in ayu HSPCs, whereas PaCXCR4a was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…CXCL12 is constitutively expressed by bone marrow stromal cells and is therefore referred to as stromal cell-derived factor-1 17 . CXCR4 is a member of the GPCR family, comprising 352 amino acid residues, and is expressed in hematopoietic stem/ progenitor, pre-B, and endothelial cells [18][19][20][21] . CXCR4 is reported to be upregulated in at least 23 different hematopoietic and nonhematopoietic tumors, including esophageal cancer [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] .…”
Section: Cxcl12/cxcr4 Axis Structure and Functionmentioning
confidence: 99%
“…CXCL12 is constitutively expressed by bone marrow stromal cells and is therefore referred to as stromal cell-derived factor-1 17 . CXCR4 is a member of the GPCR family, comprising 352 amino acid residues, and is expressed in hematopoietic stem/ progenitor, pre-B, and endothelial cells [18][19][20][21] . CXCR4 is reported to be upregulated in at least 23 different hematopoietic and nonhematopoietic tumors, including esophageal cancer [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] .…”
Section: Cxcl12/cxcr4 Axis Structure and Functionmentioning
confidence: 99%
“…Our results indicate that cxcr4bs and cxcl12as should play a dominant role in immune response and confirm the specific ligand-receptor recognitions of Cxcl12b and Cxcr4a ( 48 , 70 ). Although derived from the common ancestor ( 71 ), the expression patterns of duplicated genes evolved divergently after separation. For example, a common carp cxcl12b ( Cccxcl12b ) exhibits highest identity with Cgcxcl12b-B , and they are both highly expressed in the brain ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian CXCR4 has been suggested as a marker for an initial common lymphoid progenitor in mice [56] and for differentiated plasmablasts or plasma cells both in mice and humans [57,58]. Several studies have analyzed the evolution and function of cxcr4 genes in teleost fish showing the presence of either two paralog genes designated as cxcr4a and cxcr4b [59][60][61] or even four gene copies in cyprinids [62]. Our results identified four different genes annotated as rainbow trout CXCR4-like, which all seemed expressed in B cells.…”
Section: Cxcr4-like 4 Genes As Key Markers For Fish B Cellsmentioning
confidence: 99%
“…On the other hand, the other two genes encoding homologues of the molecule previously designated as CXCR4a (LOC110516585 and LOC110530627) showed differential expression in cluster 1 and cluster 5, respectively. A previous study in fish pointed to the duplication of CXCR4 genes in teleosts evolving to a gene subfunctionalization that may stabilize the immune system controlling teleost hematopoietic stem/progenitor cell (HSPC) homeostasis [61]. In addition, these authors suggested that HSPCs expressing CXCR4a preferentially bind LPS, whereas those expressing CXCR4b preferentially bind SDF-1 reflecting different pathways of immune cell differentiation [61].…”
Section: Cxcr4-like 4 Genes As Key Markers For Fish B Cellsmentioning
confidence: 99%
See 1 more Smart Citation